Game Theory From Idea to Practice - Sobota, Branislav (IntechOpen, 2023)
Games both as activities and as a basic educational tool are important not only from birth to death, but also from the beginnings of human society to the present day. This book describes some modern game approaches, procedures and algorithms, as well as the practical use of game theory and its development. The discipline of game theory deals mainly with types, description, algorithmization and strategies, but also the formalization of games. Among other topics, the book discusses game classifications and formalization, cooperative and non-cooperative games, symmetric and asymmetric games, simultaneous and turn-based (sequential) games, and games with complete and incomplete information. The book also considers the testing and presentation of games, the relationship of game theory and information technologies, of strategy games and sports games, of economy and business games theory, and the educational, training and sociological impacts of gaming.